2010
DOI: 10.1152/jn.00478.2010
|View full text |Cite
|
Sign up to set email alerts
|

How Global Are Olfactory Bulb Oscillations?

Abstract: Previous studies in waking animals have shown that the frequency structure of olfactory bulb (OB) local field potential oscillations is very similar across the OB, but large low-impedance surface electrodes may have favored highly coherent events, averaging out local inhomogeneities. We tested the hypothesis that OB oscillations represent spatially homogeneous phenomena at all scales. We used pairs of concentric electrodes (200 μm outer shaft surrounding an inner 2-3 μm recording site) beginning on the dorsal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…These data underlie current hypotheses that the OB, in addition to processing the information content of primary sensory inputs, also transforms the metric of this sensory information from a rate-coded basis among primary olfactory sensory neurons (OSNs) into a sparser, spike timing-based representation at the output of the OB [17][18][19][20][21] , thereby gaining the attendant advantages of this coding scheme 1 . Implicit in these theories of timing-based computation in the OB, critically, is the principle that gamma oscillations are substantially coherent across the entire olfactory bulb 20,22,23 . However, the capacity for such broad coherence is challenged by the heterogeneity in activation levels among mitral cells that encodes odor identity and other limitations of the dynamical systems presently proposed to underlie OB oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…These data underlie current hypotheses that the OB, in addition to processing the information content of primary sensory inputs, also transforms the metric of this sensory information from a rate-coded basis among primary olfactory sensory neurons (OSNs) into a sparser, spike timing-based representation at the output of the OB [17][18][19][20][21] , thereby gaining the attendant advantages of this coding scheme 1 . Implicit in these theories of timing-based computation in the OB, critically, is the principle that gamma oscillations are substantially coherent across the entire olfactory bulb 20,22,23 . However, the capacity for such broad coherence is challenged by the heterogeneity in activation levels among mitral cells that encodes odor identity and other limitations of the dynamical systems presently proposed to underlie OB oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…Bullock and McClune (1989) reported finding no difference in coherence when comparing electrode recording sites with 1-m diameters to those with 50-m diameters or when comparing those with 25-m diameters to those with 250-m diameters. Kay and Lazzara (2010) later compared coherence between electrodes of very different sizes (200-vs. 2-to 3-m diameters). They found that the much larger electrodes reported slightly more coherence, although the spectral power was the same between the different electrode sizes.…”
mentioning
confidence: 99%
“…Gamma oscillations are thought to be more spatially localized to individual cortical areas and even parts of these areas, while beta oscillations are thought to represent a coordinated oscillation supported by bidirectional connections between OB and PC (Martin et al, 2006; Kay et al, 2009; Kay and Lazzara, 2010). Curiously, we found that aPC beta power was not significantly reduced when OB beta was reduced by scopolamine, but aPC gamma was significantly reduced when ipsilateral OB gamma was suppressed by infusion of APV (Fig.…”
Section: Discussionmentioning
confidence: 99%